Turn-taking in the Classroom Session in the Movie Freedom Writers by Richard La Gravanese (2007) - Wahyu Aji Pradana; Malikatul Laila (Ethical Lingua: Journal of Language Teaching and Literature, 2020)
Speaker (S) and next speaker or hearer (H) requires a turn-taking process in order to obtain the desired information. This study aims (1) to determine the rules of turn-taking used by S and H in Classroom sessions in the film "Freedom Writers" and (2) to explain the intention of turn-taking in the Classroom session done in the film "Freedom Writers". The data of this study were the utterances and action which were taken from activities during the class session in the film "Freedom Writers" by Richard La Gravanese (2007). To analyze the data, the researcher refers to Sacks, Schegloff, & Jefferson’s (1974) theory about turn-taking rules. The researcher determines the intention by referring Cutting’s theory about pragmatics such as context and conversation analysis. The result of study shows that (1) turn-taking 1A (S chooses H in the speech) is the highest, (2) turn-taking 1B (H is not chosen by S) is the second higher; and turn-taking 1C (S can stop or continue speaking) is the least in frequencies. It can be concluded that the rule 1A is dominant and is often used in turn-taking in classroom session. (2) The researcher found that the intention within the turn taking are ranged from the highest to the lowest respectively : to ask , to clarify, to demand, to inform, to assert, to support, to request, to invite, to threat, to challenge, and to tease. Therefore, it can be concluded that the intention to ask is the most intention used in classroom session.